Effect of magnetothermal force on heat and fluid flow of paramagnetic liquid flow inside a pipe. (25th March 2017) - Kaneda, Masayuki; Tsuji, Akira; Suga, Kazuhiko
Highlights: Magnetothermal force works like a rib on inner perimeter of the heated pipe. The rib-effect exists in front of the magnet. Magnetic field of a solenoid coil induces a vortex in the coil region. Heat transfer of paramagnetic fluid is enhanced behind the magnet. Abstract: Three-dimensional numerical simulations are carried out for a pressure-driven laminar pipe flow of paramagnetic liquid heated from the pipe wall at a constant heat flux. In the presence of an external magnetic field by a single-turn electric coil, the fluid flow is directed to the center axis and the thermal boundary layer becomes thick ahead the coil. Behind the coil, the flow is reattached and the thermal boundary layer becomes thin. The local heat transfer is correspondingly suppressed and enhanced near the coil. These become remarkable in case of coil placed at downstream. The magnetothermal force also contributes to the flow rate corresponding to the coil location. It is concluded that the force by a single coil works like a rib at inner perimeter. The magnetothermal force is further examined for a solenoid coil. It is found that when both solenoid ends are covered by the heating region, the solenoid blocks the heat and fluid flow at the upstream solenoid end. A stagnant flow region is induced in the solenoid-overlapping area. The heat transfer enhancement can be expected when the solenoid is long enough so that the upstream solenoid end is ahead of the heating region. These suggest the heat transfer is enhanced behind the magnet, which is validated by an experiment. To confirm the effect in the gravity field, corresponding numerical simulations are carried out considering buoyancy.